(3TQM LeY GdLhGeYs - (3LdGd GdOjf eMeO Hf CMeO GdeMdi GdTGaYjs; (3JGL GdOjf GdSHcj , CHh fUQ,J (B771 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi CaVGdg gPG eG ETJOJ Edjg MGLI GdeJagejf HLeY GdLhGeY ef (B[ (3TQM jMd (B] (3CdaGXg , hjHjf eQGOg s
(3BNQgG (B:s
(3Gddge jG PG GdaVd GdYXje JaVd YdjfG HGdYah , hHeGJTGA ef GdfYje hGdMeO ddg QH GdYGdejf hgPG BNQ eG ETJed Ydjg GdcJGH s
(3HgG fXGe GdJYbjHIs
(3YdjgG JUMjMGJ cKjQI hjHOh CfgG HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3CUhd Gdabgs